Toward high-speed visible laser lighting based optical wireless communications. (September 2019) - Tsai, Cheng-Ting; Cheng, Chih-Hsien; Kuo, Hao-Chung; Lin, Gong-Ru
Abstract: Visible wavelength light-emitting diodes (LEDs) and laser diodes (LDs) enabled optical wireless communication (OWC) is an emerging technology for realizing high-confidentiality and high-speed point-to-point (PtP), vehicle-to-vehicle, and white-lighting data access links in indoor/outdoor free-space and underwater environments. Notably, OWC facilitates users to access more transmission bandwidth and capacity with physical-layer security and electromagnetic-immunity features by utilizing unlicensed visible optical carriers bands covering from 400 to 800 THz as compared to the commonly employed radio-frequency bands. Hence, a large amount of heavy data exchanging, routing, and streaming traffics can be realized in the current wireless networks. This also reinforces the realistic fusion of optical fiber wireline, radio-frequency wireless, and visible lighting communication networks in the new big-data era. In this paper, developing progress as well as the current trend of visible LED and LD based OWC networks for PtP, white-lighting and underwater applications are overviewed in detail. The performance parameters and figures-of-merits of previously reported OWC systems are summarized for comparison and discussion. Three main scenarios including visible LED based lighting OWC, visible LD enabled PtP communication, and LD based white-light fidelity ("Li-Fi") are individually discussed and summarized with their allowable data rate, transmission distance, and lighting color temperature and rendering index for comparison. At first, the transmission performances of LED based PtP and white-lighting OWC system with the use of novel data formats, such as pulse amplitude modulation and quadrature amplitude modulation-orthogonal frequency division multiplexing, are surveyed to understand the increasing trend on transmission capacity of LED based OWC system. Owing to the limited bandwidth and data rate of LED based OWC system, the LD has gradually been regarded as a competitive alternative candidate transmitter due to their significantly broadened bandwidth and enhanced data capacity. By taking the aforementioned advantages, studies on the blue/violet LD based white-lighting OWC have recently emerged to demonstrate the substitutability of this technology. The impacts of LD based OWC technology with its state-of-the-art implementation are comprehensively discussed together with prospects for future developments. Undoubtedly, the blue/violet LDs are also a promising transmitter for underwater PtP transmission owing to its extremely low power extinction in water, which has recently emerged as the most intriguing source for undersea exploration and sensing applications.